Evaluation of detonation performance of explosives ICM-101, ONC, and TNAZ based on improved VHL equation of state - Yong Han; Qin Liu; Yingliang Duan; Yaqi Zhao; Xinping Long (Defence Technology)
Detonation performance is crucial for evaluating the power of high explosives (HEs), and the equation of state (EOS) that accurately describes the high-temperature, high-pressure, and high-temperature, medium-pressure states of detonation products is key to assessing the damage efficiency of these energetic materials. This article examines the limitations of the VLW EOS in representing the thermodynamic states of explosive detonation gas products under high-temperature and medium-to high-pressure conditions. A new gas EOS for detonation products, called VHL (Virial-Han-Long), is proposed. The accuracy of VHL in describing gas states under high-temperature and medium-to high-pressure conditions is verified, and its performance in evaluating explosive detonation and working capabilities is explored. The results demonstrate that VHL exhibits high precision in calculating detonation performance. Subsequently, the detonation performance of three new HEs (ICM-101, ONC, and TNAZ) was calculated and compared to traditional HEs (TATB, CL-20, and HMX). The results indicate that ONC has superior detonation performance compared to the other explosives, while ICM-101 shows a detonation velocity similar to CL-20 but with slightly lower detonation pressure. The detonation characteristics of TNAZ are comparable to those of the standard HE HMX. From the perspective of products, considering the comprehensive work performance (mechanical work and detonation heat), both ONC and ICM-101 demonstrate relatively superior performance.